Report of the Study Team on Prohibition Volume II, Government of India - Planning Commission (Planning Commission, 1964)
The First Volume covered 45 chapters and the present Volume contains 25 chapters. The principal scope of the Second Volume is the examination of the local problems, of each State and Union Territory separately. It has been noticed that the problems in the way of effective enforcement of prohibition do not follow the same pattern in all States. Each chapter relating to an individual State is self-contained and cross references have been avoided. This has inevitably led to some repetition particularly in respect of suggestions given for implementation of prohibition. These chapters have been arranged under separate Sections which deal with (i) dry States; (ii) partially dry States; (iii) wet States; (iv) Union Territories. This is followed by six general chapters. A number of jails in different States were visited, and the Team had talks with male and female prisoners undergoing prison sentences for infringement of liquor laws. The discussions with the convicts were free and unembarrassed and certain important practices, the modes of committing breaches of law and the.system of bribery were frankly disclosed by them. These statements have been summarised aid the disclosures made therein are instructive. The prisoners threw light on matters hitherto obscure. Most of their information was at first hand. This has been considered in Chapter LXIV which also contains a reference to predisposing and exciting causes giving rise to drinking propensities.
Report of The Study Team on Prohibition Volume II
Government of India